# 2017-fall-122-hmwk-02-01-soln

```Math 122 Pset 2
1
Subgroups of the integers, and their cosets
(a) We need to show that nZ contains the identity 0 and is closed under inverses and multiplication: 0 = 0n ∈ nZ
shows that nZ contains the identity for any n.
Let x, y ∈ nZ. We will next show that x−1 and x + y are in nZ. If x, y ∈ nZ, there exist a, b ∈ Z such that x =
an, y = bn. Then x−1 = (−a)n ∈ nZ shows that nZ is closed under inverses, and x + y = an + bn = (a + b)n ∈ nZ
shows that nZ is closed under the multiplication operation.
(b) Let H be a subgroup of Z. First, note that if H is the zero subgroup, it is already of the form nZ, namely for
n = 0.
Otherwise, assume that H is not the zero subgroup. First, we argue that H must have at least one positive
number. Suppose otherwise. Since H is not the zero subgroup, it must have at least one negative, non-zero
number; call this number −a. The inverse of −a must be in H, so (−a)−1 = a ∈ H. But then a &gt; 0, so H must
have at least one positive number.
Consider the smallest positive number in H; call this number n. We will show that H = nZ.
We will quickly show that, since H is closed under multiplication, an and (−a)n must be in H for any positive
number a. First, we have the base case, a = 1; then an = n ∈ H, and (−a)n = −n ∈ H, since H must be closed
under inverses. For the inductive case, assume that a = N for some fixed N , and that an ∈ H. We wish to
show that (a + 1)n ∈ H. But (a + 1)n = an + n; we already know that an, n ∈ H, and H must be closed under
multiplication, so we know that (a + 1)n ∈ H. But then −(a + 1)n = (−a − 1)n ∈ H as well, since H must be
closed under inverses. Thus, we know that an ∈ H for any a ∈ Z, so nZ ⊂ H.
It remains to show that H ⊂ nZ. Suppose otherwise. Then there exists a number x ∈ H such that x = an + b,
where a, b ∈ Z, 0 &lt; b &lt; n. Since H is closed under multiplication, −an + (an + b) ∈ H, so (−an + an) + b ∈ H,
so b ∈ H. But if b ∈ H, then n is not the smallest positive number in H, and we have a contradiction. Thus,
H ⊂ nZ, so we have H = nZ.
(c) First, let us deal with the case where n = 0. Then, for any g ∈ Z, gH = {g}, so Z/H =
{{0, }, {−1}, {+1}, {−2}, {+2}, &middot; &middot; &middot; }.
Next, assume that n 6= 1. Then, for any given g ∈ Z, gH = {g, g &plusmn; n, g &plusmn; 2n, &middot; &middot; &middot; }. In particular, if |g| ≥ n,
there exists an element g 0 ∈ gH such that 0 ≤ g 0 &lt; n (found by adding n or −n to g until the sum is within the
correct range). Thus, gH = g 0 H, so the orbits are uniquely defined by elements in the range [0, n).
So the elements of Z/H are therefore {{0, &plusmn;n, &plusmn;2n, &middot; &middot; &middot; }, {1, 1 &plusmn; n, 1 &plusmn; 2n, &middot; &middot; &middot; }, &middot; &middot; &middot; , {(n − 1), (n − 1) &plusmn; n, (n −
1) &plusmn; 2n, &middot; &middot; &middot; }}. This set is isomorphic to Z/nZ; the function f : Z/nZ → Z/H, x 7→ {x, x &plusmn; n, x &plusmn; 2n, &middot; &middot; &middot; } is a
bijection.
```